Design of a Golf Putting Pneumatic Mechanism Integer vs Fractional Order PID - Couceiro, Micael S.; Figueiredo, Carlos M.; Dias, Gonçalo; Machado, Sara M.; Ferreira, Nuno M. F. (IntechOpen, 2012)
None